Economic and marketing analysis of smallholder broiler production in Mopani District of Limpopo Province, South Africa - Machethe, Tanya Ashley (University of Limpopo, 2016)
The broiler industry in South Africa consists of both small-scale and commercial poultry farmers. It provides the cheapest source of protein, absorbs labour and contributes massively to the agricultural sector. Broiler industry absorbs labour from the labour market, both skilled and unskilled; therefore it is a good source of employment. The specific objectives of the study included determining factors influencing productivity among smallholder broiler producers in Mopani District using Stochastic Frontier Production Function and technical efficiency analysis. The profitability of smallholder broiler production in the study area was also estimated using the Gross Margin Analysis. Furthermore, determinants of market participation among smallholder broiler producers in the study area were analysed using the Logit model. The Stochastic Frontier Production Function results revealed a positive relationship between the productivity of the farmers in their broiler production and labour, feeds, stock size and vaccines. The results also showed that feeds was significant at 1% while stock size was significant at 10% level. The technical efficiency results indicated that smallholder broiler farmers in Mopani District could save an average of 23.4 % in production costs and realize a maximum cost saving of 95.8% in production costs. The Gross Margin Analysis revealed that the cost of feeds were the highest incurred, taking up 70.61% of the total costs of production and the second highest being cost of stock comprising of 15.11% of the total production costs. The Logit results on the determinants of market participation showed that household size, income received per month, experience, land size, access to market information, distance to the market, profitability and land ownership are statistically significant in determining participation in the market. Based on the findings from the study, it is recommended that linkages between the formal markets and the smallholder farmers be established for farmers not participating in the market. Farmers who making profit and have more experience in broiler production should be provided with a platform to grow into commercial farming. This could be through subsidies or provision of other incentives that are key to enhancing expansion, such as land and funds.
Thesis (MSc. (Agricultural Economics)) -- University of Limpopo, 2016
Keywords: Broiler industry; Commercial poultry farmers; Poultry breeding -- South Africa; Chicken industry